A Concise, User-friendly Guide to Conducting and Reporting Scoping Reviews in Healthcare - Gill, Paul (Pacific Rim International Journal of Nursing Research, 2021)
Scoping reviews are increasingly common in healthcare, including in nursing. However, unlike systematic reviews, they remain a somewhat newer entity. Therefore, there is still some uncertainty regarding what scoping reviews are, and when and how they should be undertaken and reported. This paper aims to clarify some of the common misconceptions associated with scoping reviews. Scoping reviews may be undertaken for many reasons, such as to map a body of literature (especially in developing areas of knowledge and practice), clarify key concepts, identify the volume of existing evidence or sometimes used as preliminary step to a systematic review. While they are similar to systematic reviews, scoping reviews are undertaken for different reasons and usually review different types of evidence. The Joanna Briggs Institute (JBI) published updated guidelines for the conduct and reporting of scoping reviews in 2020 and to ensure consistency and rigour, all scoping reviews should now be conducted using such guidelines. This paper provides a concise overview of when scoping reviews are indicated and how they should be conducted and reported.